Cognition in older adults with bipolar disorder: An ISBD task force systematic review and meta‐analysis based on a comprehensive neuropsychological assessment. (7th January 2022) - Montejo, Laura; Torrent, Carla; Jiménez, Esther; Martínez‐Arán, Anabel; Blumberg, Hilary P.; Burdick, Katherine E.; Chen, Peijun; Dols, Annemieke; Eyler, Lisa T.; Forester, Brent P.; Gatchel, Jennifer R.; Gildengers, Ariel; et al.
Abstract: Objectives: We aim to characterize the cognitive performance in euthymic older adults with bipolar disorder (OABD) through a comprehensive neuropsychological assessment to obtain a detailed neuropsychological profile. Methods: We conducted a systematic search in MEDLINE/Pubmed, Cochrane, and PsycInfo databases. Original studies assessing cognitive function in OABD (age ≥50 years ) containing, at a minimum, the domains of attention/processing speed, memory, and executive functions were included. A random‐effects meta‐analysis was conducted to summarize differences between patients and matched controls in each cognitive domain. We also conducted meta‐regressions to estimate the impact of clinical and socio‐demographic variables on these differences. Results: Eight articles, providing data for 328 euthymic OABD patients and 302 healthy controls, were included in the meta‐analysis. OABD showed worse performance in comparison with healthy controls, with large significant effect sizes (Hedge's g from −0.77 to −0.89; p  < 0.001) in verbal learning and verbal and visual delayed memory. They also displayed statistically significant deficits, with moderate effect size, in processing speed, working memory, immediate memory, cognitive flexibility, verbal fluency, psychomotor function, executive functions, attention, inhibition, and recognition (Hedge's g from −0.52 to −0.76; p  < 0.001), but not in language and visuoconstruction domains. None of the examined variables were associated with these deficits. Conclusions: Cognitive dysfunction is present in OABD, with important deficits in almost all cognitive domains, especially in the memory domain. Our results highlight the importance of including a routine complete neuropsychological assessment in OABD and also considering therapeutic strategies in OABD.